EKSPEKTASI DAN MOTIVASI ORANG TUA MENYEKOLAHKANANAK DI SMA MUHAMMADIYAH 1 SURAKARTA KELAS XITAHUN PELAJARAN 2016/2017 - Isnaini, Fatimah; , Dra. Mahasri Shobahiya, M.Ag (2017)
Each person would have the best hope for the future of their children. To achive the expectations parent have a set of measure for children in the form of achievement, competence and skill and character quality in order to answer all the challenges of the times are always on going dynamic. Islamic educational institutions is one of the alternatives for parents to choose their children's education, where institutions of Islamic education is an educational institution that combines general education and religious education. Based on this, the formulation of the problem in this research is how the expectations and motivation of parents to send children in SMA Muhammadiyah 1 Surakarta? This study aimed to describe the expectations and motivation of parents to send children in SMA Muhammadiyah 1 Surakarta. This research is a field research with qualitative descriptive approach. This research subject is the parent class XI SMA Muhammadiyah 1 Surakarta in 2016/2017 taken by snowball sampling. Methods of data collection in this study, using interviews and documentation. Data analysis technique used is descriptive qualitative, ie the data obtained is then poured in the form of words or pictures, then described so as to provide clarity fact realistic. The results of this study found that the expectation of parents to send children in SMA Muhammadiyah 1 Surakarta class XI of the school year 2016/2017 is to have a child morality, so that children can understand the Qur'an, so that their religious knowledge and her child to be a child achievement. The motivation of parents to send children in SMA Muhammadiyah 1 Surakarta class XI of the school year 2016/2017 is due to the curriculum, the school's vision and mission, facilities and infrastructure, accomplishments and education expenses.